Image potential state Influence on Charge Exchange in Li+ - Metal Surface Collisions - Bonetto, Fernando Jose (2014)
The energy dependence of the neutral fraction of ions scattered by metal surfaces is observed to be affected by the presence of energy gaps and surface states in their surface band structure. The effect is more dramatic when the ion energy level remains close to the surface Fermi level of the surface, as it occurs in the scattering of Li positive ions by Cu and noble metal surfaces. We have incorporated the interaction of the ion state with the bulk- and surface-like states within an extended Anderson model and by using an ab initio calculation of the Hamiltonian terms. In this form we found that the increase of the neutral fraction at low projectile energies is explained solely by the presence of energy gaps in the case of Cu(111), while the bonding interaction with the first image potential state is also important in the Cu(100), Ag(100), and Ag(111) surfaces.